Comparison of Molecular vs. Conventional Methods for Detection of Helicobacter Pylori: A Study of 140 Patients - Ghazala Zarin Afridi, Muhammad Ilyas, Rahila Bano, Shazia Tariq, Inam Ullah Wazir, Wajeeha Zarin Afridi, (Pakistan Journal of Medical & Health Sciences, 2024)
Background: Helicobacter pylori (H. pylori) is a major cause of gastrointestinal diseases, including peptic ulcers and gastric cancer. Accurate detection methods are critical for diagnosis and treatment. This study compares molecular methods (Polymerase Chain Reaction [PCR] and Urea Breath Test [UBT]) and conventional methods (Stool Antigen Test, Serological Test, Endoscopy with Biopsy) in detecting H. pylori in 140 patients. Methods: 140 patients suspected of H. pylori infection were enrolled and underwent diagnostic testing using PCR, UBT, Stool Antigen Test, Serology, and Endoscopy with Biopsy. Results were compared across methods to assess sensitivity, specificity, and diagnostic accuracy. Results: PCR and UBT demonstrated high sensitivity (92% and 89%, respectively), with Endoscopy and Biopsy providing the highest specificity (95%). The Stool Antigen Test showed moderate sensitivity (81%) but was cost-effective. Serological tests had the lowest sensitivity but provided a simple and quick method for detecting past infections. Conclusion: Molecular methods (PCR and UBT) offer high accuracy in detecting H. pylori, especially in patients with active infection, while conventional methods, though less sensitive, remain effective and more accessible for diagnosis and treatment monitoring.